PERANCANGAN COWPER GUNA PEMANFAATAN GAS BUANG PELEBURAN LOGAM - Yoska Octaviano; Yusep Mujalis; Benny Siantury; Tono Sukarnoto; Rianti Dewi Sulamet (Jurnal Ilmiah Teknik Mesin POROS, 2014)
Abstract: A prototype of homemade furnace was built and the highest temperature it can reach during the trial process is approximately 400OC. Beside liquid metal, the furnace also produced exhaust gas as a side product. The exhaust gas is still hot. Hot gas can be used to improve the furnace’s temperature based on blast furnace method. To apply this method, the furnace should be companied with cowper. In designing cowper, several parameters should be notice. The parameters are hot gas temperature, air flow direction, and its movement ability with the furnace. Hot gas temperature will determine the number of heat absorber layers. The direction of the air flow will determine the cowper construction. Movement ability is associated with space. The design is made based on VDI 2221. The cowper design concept is cowper to store hot gas made of ramming refectories with its outer diameter similar to oil tank and the movement mechanism only applied for migration.